PENGARUH PENERAPAN PRINSIP-PRINSIP PEMBIAYAAN PENDIDIKAN TERHADAP KUALITAS PENDIDIKAN DI SDN LEYANGAN - Zulianti Lisa Kurniawati; Emmelia Maria Sulistyorini; Riska Bhinita Sari; Nurkolis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education is one of the main pillars in the development of a nation, where the quality of education in elementary schools is very crucial. This study aims to analyze the effect of the application of educational financing principles on the quality of education in elementary schools. The methodology used is a case study at SDN Leyangan, with data collection through interviews, observations, and document analysis. The main findings indicate that the application of transparent and accountable educational financing principles contributes positively to improving the quality of education, including student achievement, learning processes, and facilities and infrastructure. The implications of this study indicate the need for better policies in school financial management in order to improve the quality of education sustainably.